Emirati Adults Have a Higher Overall Knowledge on Vitamin D Compared to Tourists - Saleh, Ahlam; Alhadhrami, Jawaher Saeed; Al Ramahi, Maei Saeed; Albloushi, Halima Ali; Hijazi, Rafiq; Abboud, Myriam; Papandreou, Dimitrios (Frontiers in Psychology, 2020)
Objectives: In the last decade, vitamin D deficiency has become a major global issue. One of the main functions of vitamin D is the proper absorption of calcium in the gastrointestinal track. Optimal vitamin D levels are mandatory for adequate calcium absorption and bone health. The purpose of this study was to assess the level of knowledge of vitamin D, calcium and physical activity among Emirati and Tourist adults in Abu Dhabi. Methods: This is a cross-sectional study that took place in three different malls in Abu Dhabi and included Emirati and tourist adults. Participants were asked to fill in a questionnaire consisting of 32 questions. These included questions on vitamin D, calcium, supplement and physical activity knowledge. Another section of the questionnaire included general information on age, sex, education, weight and height. The collected data were statistically analyzed using descriptive statistics using IBM SPSS statistics for windows version 26.0 (SPSS Inc., Chicago, IL). Statistical significance was set at P<0.05. Results: Out of hundred forty-seven adults 113 were females and 34 males. The mean age, height and weight were 27.9±8.6, 162.7±10.4 and 66.5±19.5, respectively. Emiratis had statistically significant higher basic knowledge on vitamin D compared to Tourists (44.9% vs 27.1%), respectively. More than 66% of the whole sample was aware that vitamin D deficiency can affect muscle strength, as well as, that calcium may affect osteoporosis. In multiple regression model to analyze the possible effects of other factors to knowledge, it was found that only age (Beta:0.045, P<0.014) and nationality (Beta: 0.750, P<0.018) were independently and significantly associated to vitamin D. Conclusion: Emirati participants showed a higher overall vitamin D knowledge than their tourist counterparts. Both groups had low/medium level of knowledge when it comes to Physical activity, Calcium and Vitamin D supplements.